Arahan Penataan Permukiman Suku Bajo Dengan Kegiatan Usaha Berbasis Rumah Tangga di Kelurahan Bajoe - Vera Vebriani; Ria Wikantari Rosalia; Wiwik Wahidah Osman (Jurnal Wilayah & Kota Maritim (Journal of Regional and Maritime City Studies), 2016)
Household business is one of the additional activities that is able to provide more income for the fishing community. Efforts by utilizing the potential of marine products become very promising activities to improve the economy of the fishing community. Bajo Tribe fishermen in the Bajoe Village live and live on the coast forming a special settlement with slum conditions without being equipped with facilities and infrastructure to support business activities. Bajo people have a business of processing seafood and selling food and daily necessities to support their daily needs apart from fishing. The Bajo people use the house and yard as a business space in a simple and limited way. One obstacle in business activities is the lack of capital and creativity owned by the community. This study aims to identify and explain the characteristics of the types of fishing community businesses, analyze the condition of the building and environmental structure, identify the availability and condition of infrastructure facilities supporting the business activities of the fishing community, and compile directions for the settlement of Bajo Tribes based on Household Enterprises (UBR) . The results of this study are in the form of direction of settlement structuring with household-based business activities in the form of institutional cooperation, development of human resources (HR), development and growth of UBR, and improving the quality of settlement facilities and infrastructure.